EVALUATION OF E-LEARNING IMPLEMENTATION IN THE UNIVERSITY USING DELONE AND MCLEAN SUCCESS MODEL - Seliana, Neni; Suroso, Arif Imam; Yuliati, Lilik Noor (Jurnal Aplikasi Manajemen, 2020)
The objectives of this study are to analyze lecturers'perceptions of the implementation of e-learning, evaluate the success of the implementation of e-learning, and analyze the factors that influence and lead to the successful implementation of e-learning in Faculty of ABC in XYZ University. This research used quantitative research. The population involved in this study was lecturers of the Faculty of ABC at XYZ University who implement e-learning. This study used Delone and McLean success model. Data analysis techniques used were descriptive and Structural Equation Modeling (SEM) SMART PLS 2.0. The sampling technique used was accidental sampling. This study involved 46 lecturers as the sample using Slovin's formula, with a significance level of 10%. Data were collected using questionnaires rated with a Likert scale. The results showed that lecturers' perceptions towards the implementation of e-learning were very good. The highest achievement in its application was found at the level of effectiveness and then followed by a semantic level and technical level. Factors that influence successful implementation of elearning include information quality, use, and user satisfaction with e-learning systems implemented.